Consumption of Luxury Fashion Brands: The Motives of Generation Y Consumers in China - Sun, Ming Wei (Auckland University of Technology, 2010)
Representing nearly half of the world’s population, Asian markets are not only dynamic but also powerful (Phau & Chan, 2003). Asian consumers have been the major contributor to the growth of the luxury markets for the past ten years and among all Asian Countries, China is currently becoming one of the most booming and profitable luxury markets (Phau & Chan, 2003; Roth, 2003). Given the scale of the Chinese market, international luxury brands must win in China to continue winning in the rest of the world. Chinese luxury product consumers buy Rolex watches and Louis Vuitton bags not simply just because of the Swiss craftsmanship or French design. Thus, it is important to understand the roots of their motives, the changing culture and values that determine the buying behaviour of the Chinese luxury consumer. This study attempts to investigate young Chinese consumers’ behaviour towards purchasing luxury fashion branded products along with the discussion on the extant literature. The current study describes the results from a survey of 309 respondents from Beijing and Shanghai in China. Due to the challenge of achieving an adequate response rate, a snowball sampling method was used in this study. Rating scale items were adopted from Wiedmann, Hennigns and Siebels (2009) study to investigate consumer motives for luxury fashion branded products. The study result indicates that there is no significant difference on consumers’ luxury consumption based on which cities they come from, consumers’ age, gender or educational background. As expected the study result confirmed financial ability is an essential factor for luxury consumption. Respondent’s study results shows respondents purchasing decisions are heavily influenced by the luxury fashion brand’s functional value. Respondents also buy luxury products in order to express their individuality and personal taste rather than fit in with their peers.
Keywords: Generation Y; Luxury fashion brands; Motives